Antimicrobial effect of a novel chitosan derivative and its synergistic effect with antibiotics - Si, Zhangyong (2021)
Cationic polymers are promising antibacterial agents since they have a low propensity for bacteria to evolve resistance, but they usually have low biocompatibility due to their hydrophobic moieties. Herein, we report a new biodegradable and biocompatible chitosan-derived cationic antibacterial polymer, 2,6-Diamino Chitosan (2,6-DAC). 2,6-DAC shows excellent broad-spectrum antimicrobial activity with minimum inhibitory concentrations (MICs) of 8-32 µg/mL against clinically relevant and multi-drug resistant (MDR) bacteria including Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii. Further, 2,6-DAC shows an excellent synergistic effect with various clinically relevant antibiotics proved by decreasing the MICs of the antibiotics against MDR A. baumannii and MRSA to <1 µg/mL. In vivo biocompatibility of 2,6-DAC is proved by a dosage of 100 mg/kg compound via the oral administration and 25 mg/kg compound via intraperitoneal injection to mice; 2,6-DAC does not cause any weight loss and any significant change in liver and kidney biomarkers nor the important blood electrolytes. The combinations of 2,6-DAC together with novobiocin and rifampicin show >2.4 log10 reduction of A. baumannii in murine intraperitoneal and lung infection models. The novel chitosan derivative, 2,6-DAC, can be utilized as biocompatible broad-spectrum cationic antimicrobial agent alone or in synergistic combination with various antibiotics.